A kind of synthetic method of polybutylene terephthalate
By using titanium catalyst to carry out a one-step reaction under a nitrogen atmosphere, the problems of harsh reaction conditions and by-products in the preparation process of polybutylene terephthalate were solved, and efficient and simple synthesis process was achieved, and the product was improved Mass and catalyst recycling capability.
Patent Information
- Application Number
- CN202410707782.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-06-03
AI Technical Summary
During the preparation process of polybutylene terephthalate, the reaction conditions are harsh, the reaction medium is highly acidic, and the reaction by-products have an adverse effect on the product quality.
Polybutylene terephthalate was prepared by using titanium catalyst as the catalytic material, and cyclic carboxylic acid and acyclic alcohol as raw material in a one-step reaction under a nitrogen atmosphere. The titanium catalyst separates from the product through a magnetic field to realize the continuous recycling of the catalyst.
The simple and efficient one-step synthesis of polybutylene terephthalate is achieved, which reduces production costs, improves product quality stability, and has good stability and recycling of catalysts.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer synthesis, and in particular relates to a method for synthesizing polybutylene terephthalate. Background Art
[0002] Polybutylene terephthalate is a polymer material with high temperature resistance, moisture resistance, good electrical insulation performance, oil resistance, chemical corrosion resistance, and fast molding. It is now mainly used in the fields of electronics, automobiles, and machinery. The known technical solutions for preparing polybutylene terephthalate are mainly divided into ester exchange method and direct esterification method. The ester exchange method uses dimethyl terephthalate and 1,4-butanediol as raw materials, first undergoes ester exchange reaction to generate dibutyl terephthalate, removes formaldehyde, and then undergoes polycondensation reaction to produce dibutyl terephthalate. There are intermittent processes and continuous processes. The intermittent process equipment is simple and easy to control, suitable for small-scale production, but the quality of each batch of products may vary, and the product quality stability is poor; the continuous process uses a tubular or screw reactor, which has high efficiency, stable quality, and is suitable for large-scale production. The direct esterification production process uses purified terephthalic acid and 1,4-butanediol as raw materials. The process is short, with low equipment investment and energy consumption, but the dehydration problem of 1,4-butanediol needs to be properly solved. Due to the harsh reaction conditions and strong acidity of the reaction medium, part of 1,4-butanediol is dehydrated and cyclized to form tetrahydrofuran, which has an adverse effect on product quality. Therefore, the direct esterification process has much higher control requirements on the reaction system than the ester exchange method. Summary of the invention
[0003] The technical solution of the present invention aims at the technical difficulties such as harsh reaction conditions, strong acidity of the reaction medium, adverse effects of reaction by-products on product quality in the preparation process of polybutylene terephthalate, and provides polybutylene terephthalate and a synthesis method thereof.
[0004] The main purpose of the present invention is:
[0005] 1. Provide a process for directly preparing polybutylene terephthalate;
[0006] Second, provide a new low-cost catalyst for the method;
[0007] 3. Ensure that the preparation process is simple and efficient and can achieve one-step synthesis.
[0008] To achieve the above objectives, the present invention adopts the following technical solutions.
[0009] A method for synthesizing polybutylene terephthalate,
[0010] The method comprises:
[0011] A titanium catalyst is used as a catalytic material, and cyclic carboxylic acid and acyclic alcohol are used as raw materials to react under a nitrogen atmosphere to prepare polybutylene terephthalate by a one-step reaction.
[0012] As a preference,
[0013] The titanium catalyst preparation method is as follows:
[0014] The catalyst preform is prepared by mixing tetrachlorobis(tetrahydrofuran)titanium, lithium magnesium (2,2,6,6-tetramethylpiperidinium) dichloride, dichloromethane and lithium bis(trimethylsilyl)amide, and reacting them under low temperature stirring in a protective atmosphere;
[0015] The catalyst preform is mixed with ferric citrate, potassium hydroxide and cycloolefin, and subjected to heat stirring reaction in a protective atmosphere. After purification by column chromatography, the titanium catalyst is dried with anhydrous sodium sulfate to obtain the titanium catalyst.
[0016] As a preference,
[0017] The tetrachlorobis(tetrahydrofuran)titanium, dichloromagnesium (2,2,6,6-tetramethylpiperidinium) lithium, dichloromethane and bis(trimethylsilyl)amide lithium are uniformly mixed in a mass ratio of (1.5-2):1:8:(1.8-2.2);
[0018] The low temperature stirring reaction is carried out at -5 to 0°C for 8 to 12 hours.
[0019] As a preference,
[0020] The catalyst preform, ferric citrate, potassium hydroxide and cycloolefin are uniformly mixed in a mass ratio of 3: (0.8-1.2): 0.3: 10;
[0021] The hot stirring reaction is carried out at 60-80° C. and stirred for 4-8 h.
[0022] As a preference,
[0023] The cyclic carboxylic acid is terephthalic acid'
[0024] The acyclic alcohol is 1,4-butanediol
[0025] The cyclic carboxylic acid and the acyclic alcohol are uniformly mixed in a mass ratio of 1: (1-1.2).
[0026] As a preference,
[0027] The titanium catalyst is added in an amount of 0.5 to 3.0 wt % of the mass of terephthalic acid.
[0028] As a preference,
[0029] The one-step reaction is carried out in a protective atmosphere at a temperature of 100 to 150° C. and a pressure of 140 to 160 kPa with stirring for 1 to 2 hours.
[0030] The core of the technical solution of the present invention is that a special catalyst is provided by the present invention, so as to realize one-step synthesis of polybutylene terephthalate with terephthalic acid and 1,4-butanediol as raw materials through direct esterification.
[0031] The titanium-based catalyst prepared in the technical solution of the present invention is solid, and the reactants and products are both in liquid phase. The titanium-based catalyst acts as a heterogeneous catalyst in this reaction. There are special active centers on the catalyst surface that can adsorb reactant molecules. These active centers cause the reactants to form unstable intermediate compounds on the catalyst surface, thereby reducing the activation energy of the original reaction, prompting the reaction to generate new pathways, and thereby accelerating the reaction rate.
[0032] In the technical solution of the present invention, the titanium-based catalyst constructs a good metal chelate structure. In this structure, there are multiple strongly coordinated oxygen atoms, and the formed metal complex enables the catalyst to form a chelate ring and include a conjugate base with movable electrons, thereby maintaining the activity of the ligand stable. For this reason, it can be ensured that the two active centers of the catalyst have a stable chemical structure.
[0033] The catalyst provided by the present invention is a binuclear catalyst, the titanium core is for efficiently catalyzing the esterification reaction, and the silicon-lithium core is for protecting the reaction from proceeding in the forward direction without producing side reactions. The titanium-based catalyst undergoes complex catalysis, and the reactants are under the dual catalytic effects of coordination space catalysis and coordination catalysis, and the active center and the reaction system always maintain coordination complexation. The titanium coordination catalysis allows the reactants to simultaneously expose Lewis acid and Bronsted acid on the catalyst surface for esterification catalysis, and there is no exposed Bronsted acid site in the reactants. When titanium is briefly linked to the reactants by means of coordination complexation, titanium is complexed with an α-bond, and the CH bond on the β-carbon atom of the reactant is disconnected to form a Bronsted acid site. Lewis acid and Bronsted acid exist simultaneously, and a catalytic active center is formed, and ester group catalysis begins. At the same time, the silicon-lithium active center adsorbs and protects the bonds of the catalytic intermediates to prevent the alcohol and the intermediates from producing etherification side reactions in the presence of water. On the one hand, the coordination number of the intermediate complex is lower than the saturation value, and there are complex vacancies, which are prone to etherification. Silicon-lithium is inserted into the coordination group space to form a new ligand, maintaining the original coordination unsaturation of the central atom and not affecting the further reaction of the esterification intermediate. On the other hand, the electron cloud density of the titanium in the new ligand center increases, becoming a hard ion with greater polarity, which enhances the catalytic activity and selectively modulates the reaction process, rate and product distribution through electronic factors.
[0034] For the technical solution of the present invention, another core point is that the catalyst prepared by the present invention can be separated from the product by a magnetic field, so as to realize the continuous recycling of the catalyst, and the magnetic field can reorganize the catalytic active center under the joint action of the coordination field. The catalyst prepared by the present invention has excellent separation performance under the drive of the binuclear catalytic center, can be magnetized under the action of an external magnetic field, and produces a magnetic response to ensure the rapid separation of the solid-phase catalyst in the reaction system. After the reaction is completed, an external magnetic field is applied, and the catalyst is quickly precipitated and separated from the system. After the external magnetic field is removed, the catalyst can be dispersed in a new system, so as to realize the rapid separation and reuse of the catalyst and simplify the recovery operation of the catalyst. The catalyst provided by the present invention can prevent the agglomeration of catalyst particles during the recovery process by the in-situ growth of the magnetic center in a magnetic field environment through organic complexation, improve the durability of the catalyst, effectively reduce the catalyst loss, and avoid the loss of active components. At the same time, the catalyst forms dendritic macromolecules by chemical anchoring, in-situ growth and physical adsorption under the action of the magnetic field, so that the catalytically active metal center will not aggregate during the catalytic reaction, and the active center is not easy to passivate due to the spatial effect. In the technical solution of the present invention, under the action of an external magnetic field, the two active centers of the catalyst are anchored inside the catalyst through coordination and covalent bonds, so that a relatively stable binding effect is formed between the two active centers. The functionally modified catalyst has the characteristics of high surface area, high dispersibility, excellent stability, and easy magnetic separation, thereby improving the regional selectivity and product yield of the reaction.
[0035] The advantages of the present invention are:
[0036] 1) The present invention provides a special heterogeneous catalyst, which can utilize an external magnetic field to recycle the catalyst, while also optimizing the catalyst performance, extending the catalyst activity time, and reducing the catalyst cost;
[0037] 2) The catalyst components provided by the present invention include titanium-based compositions and metal compositions, do not contain heavy metal antimony, organic tin compounds and rare earth elements, and are non-toxic or low-toxic catalyst systems that have no effect on human health and the ecological environment;
[0038] 3) The catalyst provided by the present invention has high catalytic activity and selectivity, reduces the occurrence of side reactions, ensures that the preparation process of polybutylene terephthalate is simple and efficient, and can achieve one-step synthesis. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0040] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0041] Example 1: A method for synthesizing polybutylene terephthalate.
[0042] The method comprises:
[0043] (1) Titanium tetrachloride, lithium magnesium (2,2,6,6-tetramethylpiperidinium) dichloride, dichloromethane and lithium bis(trimethylsilyl)amide were mixed uniformly in a mass ratio of 1.5:1:8:1.8, and stirred for 8 h in a nitrogen atmosphere at a temperature of -5°C to prepare a catalyst preform; the catalyst preform, ferric citrate, potassium hydroxide and cycloolefin were mixed uniformly in a mass ratio of 3:0.8:0.3:10, and stirred for 8 h in a nitrogen atmosphere at a temperature of 60°C. After purification by column chromatography, the mixture was dried with anhydrous sodium sulfate to prepare a titanium-based catalyst;
[0044] (2) Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1, and a titanium-based catalyst in an amount of 3.0 wt% of the mass of terephthalic acid was added. The mixture was stirred and reacted for 2 h in a nitrogen atmosphere at a temperature of 100 °C and a pressure of 160 kPa to prepare polybutylene terephthalate by a one-step reaction.
[0045] (3) The prepared polybutylene terephthalate was cooled to room temperature and the pressure was released. The composition of the reaction liquid was analyzed using an Agilent-7820 gas chromatograph, indicating that the conversion rate of terephthalic acid was 87.5%, the yield of polybutylene terephthalate was 78.4%, and the calculated selectivity of polybutylene terephthalate was 89.6%.
[0046] The conversion rate of terephthalic acid is calculated by the following formula:
[0047] Terephthalic acid conversion rate = 100% - (remaining amount of terephthalic acid in the recycled material / amount of terephthalic acid used) × 100%
[0048] The yield of polybutylene terephthalate was calculated by the following formula:
[0049] Polybutylene terephthalate yield = (actual molar amount of polybutylene terephthalate obtained / maximum molar amount of polybutylene terephthalate that can be converted based on terephthalic acid) × 100%;
[0050] The selectivity of butylene phthalate was calculated by the following formula:
[0051] Butylene phthalate selectivity = (butylene phthalate yield / terephthalic acid conversion rate) × 100%.
[0052] Example 2: A method for synthesizing polybutylene terephthalate.
[0053] The method comprises:
[0054] (1) Titanium tetrachloride, lithium magnesium (2,2,6,6-tetramethylpiperidinium) dichloride, dichloromethane and lithium bis(trimethylsilyl)amide were mixed uniformly in a mass ratio of 1.75:1:8:2, and stirred for 10 h in a nitrogen atmosphere at a temperature of -2.5 °C to prepare a catalyst preform; the catalyst preform, ferric citrate, potassium hydroxide and cycloolefin were mixed uniformly in a mass ratio of 3:1:0.3:10, and stirred for 6 h in a nitrogen atmosphere at a temperature of 70 °C. After purification by column chromatography, the mixture was dried with anhydrous sodium sulfate to prepare a titanium-based catalyst;
[0055] (2) Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and a titanium-based catalyst in an amount of 1.75 wt% of the mass of terephthalic acid was added, and the mixture was stirred for reaction for 1.5 h under a nitrogen atmosphere at a temperature of 125 °C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction.
[0056] (3) The prepared polybutylene terephthalate was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed using an Agilent-7820 gas chromatograph. The calculation method of Reference Example 1 showed that the conversion rate of terephthalic acid was 88.3%, the yield of polybutylene terephthalate was 79.6%, and the calculated selectivity of polybutylene terephthalate was 90.1%.
[0057] Example 3: A method for synthesizing polybutylene terephthalate.
[0058] The method comprises:
[0059] (1) Titanium tetrachloride, lithium magnesium (2,2,6,6-tetramethylpiperidinium) dichloride, dichloromethane and lithium bis(trimethylsilyl)amide were mixed uniformly in a mass ratio of 2:1:8:2.2, and stirred for 8 h in a nitrogen atmosphere at 0 °C to prepare a catalyst preform; the catalyst preform, ferric citrate, potassium hydroxide and cycloolefin were mixed uniformly in a mass ratio of 3:1.2:0.3:10, and stirred for 4 h in a nitrogen atmosphere at 80 °C. After purification by column chromatography, the mixture was dried with anhydrous sodium sulfate to prepare a titanium-based catalyst;
[0060] (2) Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.2, and a titanium-based catalyst in an amount of 0.5 wt% of the mass of terephthalic acid was added, and the mixture was stirred for reaction for 1 h in a nitrogen atmosphere at a temperature of 150 °C and a pressure of 140 kPa to prepare polybutylene terephthalate by a one-step reaction.
[0061] (3) The prepared polybutylene terephthalate was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed using an Agilent-7820 gas chromatograph. The calculation method of Reference Example 1 showed that the conversion rate of terephthalic acid was 86.8%, the yield of polybutylene terephthalate was 78.3%, and the calculated selectivity of polybutylene terephthalate was 90.2%.
[0062] Application example: Referring to the titanium catalyst prepared in step (1) of Example 2, a magnetic field was used to filter out the special catalyst prepared by the present invention, and multiple catalytic application experiments were carried out to prepare multiple batches of polybutylene terephthalate. The specific process and parameters for the preparation of polybutylene terephthalate refer to the process of step (2) in Example 2. The specific characterization results are as follows.
[0063]
[0064] In addition, PBAT resins were prepared by screw extrusion from 15 groups of polybutylene terephthalate prepared in the application examples, and the performance of the PBAT resins was tested and the average value was calculated. At the same time, the same performance test was performed on commercially available PBAT resins, and the specific characterization results are shown in the following Tables Y1-1 and Y1-2.
[0065]
[0066]
[0067] By analyzing the above characterization results, it can be concluded that during the 10-time recycling of the catalyst of the present invention, the conversion rate and yield are relatively high, which proves that the special catalyst prepared by the present invention has excellent catalytic activity and catalytic stability. Although the yield of polybutylene terephthalate decreases after 10 times, the polybutylene terephthalate selectivity is still maintained at a relatively high level. It can be seen that the catalytic material in the technical solution of the present invention has good chemical stability. It can be seen that the catalyst used in the present invention has a high stability in use and can effectively achieve directional conversion even if used for a long time.
[0068] In addition, the mechanical properties of the PBAT resin prepared from polybutylene terephthalate prepared in the application example are analyzed and compared with the mechanical properties of the commercially available PBAT resin. Since the crystallinity of the PBAT resin prepared in the application example is weaker than that of the commercially available resin material, the resin material prepared in the application example has a stronger tensile strength and the toughness of the resin material is partially enhanced. At the same time, the PBAT resin prepared in the application example and the commercially available PBAT resin are subjected to light aging tests at the same time. The commercially available resin turns yellow obviously after aging treatment, but the PBAT resin prepared in the application example is only slightly yellow. After the PBAT resin prepared in the application example is activated by the catalyst, the permeability of polybutylene terephthalate in the PBAT resin material is improved, and the crystal distribution arrangement inside the material is more compact, so that the PBAT resin will not appear in a high elastic state when the temperature rises, and the melting point temperature of the resin material is increased.
[0069] Comparative Example 1: A method for synthesizing polybutylene terephthalate.
[0070] The method comprises:
[0071] Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and 1.75 wt% of commercially available dibutyltin dilaurate based on the mass of terephthalic acid was added, and the mixture was stirred for reaction for 1.5 h under a nitrogen atmosphere at a temperature of 125°C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction. The mixture was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed by gas chromatography using an Agilent-7820. Referring to the calculation method of Example 1, the results showed that the conversion rate of terephthalic acid was 73.6%, the yield of polybutylene terephthalate was 64.5%, and the selectivity of polybutylene terephthalate was calculated to be 87.6%.
[0072] Analysis of the above calculation results shows that commercially available dibutyltin dilaurate is in liquid phase, which is inconvenient to recover as a homogeneous catalyst in the comparative example. The catalyst and product are mixed, and the expected efficient utilization of the catalyst cannot be achieved in this comparative example. In addition, during the recovery of the tin-based catalyst, the impurities contained in the catalytic exhaust gas will cause the activity and selectivity of the tin catalyst to drop significantly or even be lost, resulting in tin catalyst poisoning.
[0073] Comparative Example 2: A method for synthesizing polybutylene terephthalate.
[0074] The method comprises:
[0075] Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and a commercially available silicone gel catalyst of 1.75 wt% of the mass of terephthalic acid was added, and the mixture was stirred and reacted for 1.5 h under a nitrogen atmosphere at a temperature of 125°C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction. The mixture was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed by gas chromatography using an Agilent-7820. Referring to the calculation method of Example 1, the results showed that the conversion rate of terephthalic acid was 68.8%, the yield of polybutylene terephthalate was 52.6%, and the selectivity of polybutylene terephthalate was calculated to be 76.4%.
[0076] Analyzing the above calculation results, the commercially available silicone gel catalyst has inconvenience in the recovery process of the homogeneous catalyst in this comparative example, resulting in the mixing of the catalyst and the product, and the expected catalyst efficient utilization effect cannot be fully demonstrated. At the same time, compared with Example 2, the catalytic activity of the silicon-based catalyst selected in the comparative example is relatively low.
[0077] Comparative Example 3: A method for synthesizing polybutylene terephthalate.
[0078] The method comprises:
[0079] Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and 1.75 wt% of commercially available tetrabutyl titanate based on the mass of terephthalic acid was added, and the mixture was stirred for reaction for 1.5 h under a nitrogen atmosphere at a temperature of 125°C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction. The mixture was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed by gas chromatography using an Agilent-7820. Referring to the calculation method of Example 1, the results showed that the conversion rate of terephthalic acid was 87.9%, the yield of polybutylene terephthalate was 63.7%, and the selectivity of polybutylene terephthalate was calculated to be 72.5%.
[0080] Analysis of the above calculation results shows that commercially available tetrabutyl titanate is in liquid phase. In this comparative example, the recovery process of the homogeneous catalyst is particularly inconvenient, and the catalyst and the product are mixed. Therefore, this comparative example fails to show the expected efficient utilization of the catalyst.
[0081] Comparative Example 4: A method for synthesizing polybutylene terephthalate.
[0082] The method comprises:
[0083] Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and 1.75 wt% of commercially available tetraisopropyl titanate based on the mass of terephthalic acid was added, and the mixture was stirred for reaction for 1.5 h under a nitrogen atmosphere at a temperature of 125°C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction. The mixture was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed by gas chromatography using an Agilent-7820. Referring to the calculation method of Example 1, the results showed that the conversion rate of terephthalic acid was 65.7%, the yield of polybutylene terephthalate was 57.2%, and the selectivity of polybutylene terephthalate was calculated to be 87.1%.
[0084] Analyzing the above calculation results, the commercially available tetraisopropyl titanate is in liquid form. As a homogeneous catalyst in the comparative example, its recovery process is relatively cumbersome and not convenient enough. At the same time, there is a mixture between the catalyst and the product, which makes it difficult for this comparative experiment to fully demonstrate the expected effect of efficient use of the catalyst. In addition, the polybutylene terephthalate prepared in the comparative example is prepared into PBAT resin. Due to the reduced crystallization rate of PBAT resin, the moldability is deteriorated. At the same time, the commercially available tetraisopropyl titanate wants to achieve excellent catalytic effects. Too much addition and the catalyst are also easily hydrolyzed, and the prepared PBAT resin has a yellower hue.
[0085] Comparative Example 5: A method for synthesizing polybutylene terephthalate.
[0086] The method comprises:
[0087] Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and 1.75 wt% of commercially available di-n-butyltin oxide based on the mass of terephthalic acid was added, and the mixture was stirred and reacted for 1.5 h under a nitrogen atmosphere at a temperature of 125°C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction. The mixture was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed by gas chromatography using an Agilent-7820. Referring to the calculation method of Example 1, the results showed that the conversion rate of terephthalic acid was 64.8%, the yield of polybutylene terephthalate was 52.6%, and the selectivity of polybutylene terephthalate was calculated to be 81.2%.
[0088] Analyzing the above calculation results, the commercially available di-n-butyltin oxide is a solid phase. As a heterogeneous catalyst in the comparative example, it should be easy to recycle in theory. However, when the catalyst is reused, side reactions will occur to generate other organic products, and the di-n-butyltin oxide will dissolve at this time. After an in-depth investigation of this comparative example, the mixing phenomenon of the catalyst and the product did not show the efficient utilization characteristics of the catalyst as expected, which to a certain extent affected the normal performance of the catalyst.
[0089] Comparative Example 6: A method for synthesizing polybutylene terephthalate.
[0090] The method comprises:
[0091] Terephthalic acid and 1,4-butanediol were uniformly mixed in a mass ratio of 1:1.1, and 1.75 wt% of commercially available tetraethoxyzirconium based on the mass of terephthalic acid was added, and the mixture was stirred for reaction for 1.5 h under a nitrogen atmosphere at a temperature of 125°C and a pressure of 150 kPa to prepare polybutylene terephthalate by a one-step reaction. The mixture was cooled to room temperature and the pressure was released. The composition of the reaction solution was analyzed by gas chromatography using an Agilent-7820. Referring to the calculation method of Example 1, the results showed that the conversion rate of terephthalic acid was 69.4%, the yield of polybutylene terephthalate was 53.3%, and the selectivity of polybutylene terephthalate was calculated to be 76.8%. At the same time, the catalyst was subjected to a secondary catalyst application test, and the composition of the reaction solution was analyzed using an Agilent-7820 gas chromatograph. Referring to the calculation method of Example 1, the results showed that the terephthalic acid conversion rate was 41.2%, the polybutylene terephthalate yield was 33.4%, and the calculated polybutylene terephthalate selectivity was 81.1%.
[0092] Analysis of the above calculation results shows that commercially available tetraethoxyzirconium is a solid phase and is used as a heterogeneous catalyst in the comparative example. After secondary recovery, the catalytic process is further investigated. In the prior art scheme, direct esterification and polycondensation will produce water during the reaction, and tetrahydrofuran will be generated when the catalyst is reused, which will not only lead to a decrease in the yield of polybutylene terephthalate, but also inhibit or even eliminate the catalytic activity of the catalyst.
Claims
1. A method for synthesizing polybutylene terephthalate, characterized in that: The method comprises: A titanium catalyst is used as a catalytic material, terephthalic acid and 1,4-butanediol are uniformly mixed in a mass ratio of 1: (1-1.2) as raw materials, and reacted in a nitrogen atmosphere to prepare polybutylene terephthalate in a one-step reaction; The titanium catalyst preparation method is as follows: The catalyst preform is prepared by mixing tetrachlorobis(tetrahydrofuran)titanium, lithium magnesium (2,2,6,6-tetramethylpiperidinium) dichloride, dichloromethane and lithium bis(trimethylsilyl)amide, stirring and reacting at -5 to 0°C for 8 to 12 hours in a protective atmosphere; The catalyst preform is mixed with ferric citrate, potassium hydroxide and cycloolefin, and subjected to heat stirring reaction in a protective atmosphere. After purification by column chromatography, the titanium catalyst is dried with anhydrous sodium sulfate to obtain the titanium catalyst.
2. The method for synthesizing polybutylene terephthalate according to claim 1, characterized in that: The tetrachlorobis(tetrahydrofuran)titanium, lithium magnesium dichloride (2,2,6,6-tetramethylpiperidinium), dichloromethane and lithium bis(trimethylsilylamide) are uniformly mixed in a mass ratio of (1.5-2):1:8:(1.8-2.2).
3. The method for synthesizing polybutylene terephthalate according to claim 1, characterized in that: The catalyst preform, ferric citrate, potassium hydroxide and cycloolefin are uniformly mixed in a mass ratio of 3: (0.8-1.2): 0.3: 10; The hot stirring reaction is carried out at 60-80° C. and stirred for 4-8 h.
4. The method for synthesizing polybutylene terephthalate according to claim 1, characterized in that: The titanium catalyst is added in an amount of 0.5 to 3.0 wt % of the mass of terephthalic acid.
5. The method for synthesizing polybutylene terephthalate according to claim 1, characterized in that: The one-step reaction is carried out in a protective atmosphere at a temperature of 100 to 150° C. and a pressure of 140 to 160 kPa with stirring for 1 to 2 hours.
Citation Information
Patent Citations
Polyester polymerization catalyst, process for producing the same and process for producing polyester therewith
CN101121779A
Polyester resin and catalyst for polyester production, process for producing polyester resin with the catalyst, polyester resin obtained with the catalyst, and hollow molded container comprising the p
CN1630674A